anonymous
  • anonymous
Given f(x)=5x+5 and g(x)=6x+1 then what is f(g(−8)) ? Given f(x)=10x+8 and g(x)=1x+4 then what is (f+g)(3)) ? Given f(x)=3x+4 and g(x)=8x+1 then what is (f−g)(0)) ?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Given f(x)=5x+5 and g(x)=6x+1, then what is f(g(−8)) ? First, substitute -8 to g(x). \(g(x)=6x+1\rightarrow g(x)=6(-8)+1\). Solve for x.
anonymous
  • anonymous
Tell me what x is, so can move to step two.
anonymous
  • anonymous
x = -47

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Good! Now, we need to substitute g(x)=-47 to f(x)=5x+5. \[f(x)=5x+5\rightarrow f(g(-8))= 5(-47)+5\]
anonymous
  • anonymous
Solve it and that's the answer. :)
anonymous
  • anonymous
-230?
anonymous
  • anonymous
Correct. :)
anonymous
  • anonymous
Can you help me with the rest ?
anonymous
  • anonymous
Given f(x)=10x+8 and g(x)=1x+4 then what is (f+g)(3)) ? this is 45? Given f(x)=3x+4 and g(x)=8x+1 then what is (f−g)(0)) ? this is -1?
anonymous
  • anonymous
Given f(x)=10x+8 and g(x)=1x+4 then what is (f+g)(3)) ? Add f(x) and g(x) first.
anonymous
  • anonymous
11x + 12
anonymous
  • anonymous
Then substitute 3 to x.
anonymous
  • anonymous
33 + 12 = 45
anonymous
  • anonymous
Oh wait, is that your answer? 45?
anonymous
  • anonymous
lol yes
anonymous
  • anonymous
I didn't see it at first. :D Yes you're right! I'll check your other answer. :)
anonymous
  • anonymous
-5x - 3 = -5(0) -3 = -3
anonymous
  • anonymous
\[3x+4-8x-1\]
anonymous
  • anonymous
\[-5x+3\] Substitute 0 to x.
anonymous
  • anonymous
-5x - 3 = -5(0) -3 = -3
anonymous
  • anonymous
Wrong. \(-5x+3\) Substitute 0 to x.
anonymous
  • anonymous
no positive 3
anonymous
  • anonymous
Yes.
anonymous
  • anonymous
Thank you can you help me with something else .
anonymous
  • anonymous
Just post another question and I'd be happy to help. :)
anonymous
  • anonymous
okay . thanks . !!!

Looking for something else?

Not the answer you are looking for? Search for more explanations.